Overcoming Technological and Institutional Barriers to Blended Learning Adoption in Teacher Training: A Case Study of Kwara State College of Education Oro - Muhinat Bolanle Bello; Alabelapo Kadir Akogun (Yayasan Adra Karima Hubbi, 2024)
Background. The successful adoption of blended learning in educational institutions is often hindered by technological and institutional barriers. These include constraints related to ICT infrastructure, digital literacy, and institutional policies, which collectively impede the implementation of blended learning methodologies. Purpose. This study aimed to investigate the institutional and technological barriers to blended learning adoption at Kwara State College of Education Oro. Specifically, it focused on assessing technological constraints, institutional policies, and digital literacy levels among educators and students. Method. A mixed-methods descriptive survey research design was employed. Simple random sampling was used to select a sample of 641 students and 90 lecturers. Data were collected using structured and unstructured questionnaires administered via Google Forms, enabling a comprehensive analysis of key trends. Results. The findings revealed significant barriers to blended learning adoption, including inadequate ICT infrastructure, low digital literacy among educators and students, and inconsistent power supply. These challenges highlight the need for targeted interventions to overcome the obstacles to blended learning implementation. Conclusion. The study recommends establishing a dedicated blended learning committee, developing clear institutional policies, and enhancing digital literacy training for both educators and students. Addressing these barriers is essential for the successful adoption of blended learning, which can improve educational outcomes and better prepare future educators for modern classrooms. Creating a supportive environment at Kwara State College of Education Oro is key to fostering the effective integration of blended learning methodologies